Comparison of rice production in an integrated rice-fish system using tilapia (Oreochromis niloticus) and common carp (Cyprinus carpio): Rice fish integration - Lokuhetti, Rumila Thilanka; Kondaramage, Rasika Sampath Kumra Hewa; Herath, Sandamali Sakunthala; Vidanapathirana, Nisansala Priyadharshani; Atapaththu, Keerthi Sri Senarathna (Indian Journal of Fisheries, 2025)
Rice and fish are globally essential staple foods. Given the common challenge of land scarcity faced by both fish farming and agriculture, integrating these practices can provide a viable solution. This study evaluated the integration of rice (Oryza sativa AT362) with tilapia (Oreochromis niloticus, T) and common carp (Cyprinus carpio, C) through four treatments: T, C, T+C (1:1 ratio) and a control (no fish), each treatment with three replicates. The stocking density was 3.75 individuals m-2. Tilapia integration significantly increased the number of leaves, panicles and tillers, resulting in a high yield of 6.7 t ha-¹ (approximately 1.6 times higher than that of control). In contrast, carp integration showed no significant improvements in these parameters. Rice growth was positively correlated with root area diameter, primarily influenced by tilapia activity. Tilapia demonstrated better growth performance compared to carp, with average survival rates of 74 and 64%, respectively. These findings highlight the potential of rice-fish integration in Sri Lanka, particularly the effectiveness of combining O. sativa (AT362) with O. niloticus. Keywords: Agriculture, Aquaculture, Diversification, Specific growth rate, Tillers